Nama-Nama Alternatif dalam Isnad Menurut Joseph Schacht - Riady, Fahmi (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2021)
Criticism of Joseph Schacht's hadith thought does not automatically undermine his theories. Even if examined further, these criticisms can be countered with a detailed and complete reading of Schacht's work. Therefore, in this article, the author tries to reveal further Schacht's theory about the arbitrarily backwards isnad which has implications for the emergence of alternative names. The unit of analysis of this article is the work of Schacht: The Origins of Muhammadan Jurisprudence. The aspects studied are: 1). arbitrarily backward isnād projection; and 2). Alternative names in isnād. In this article the author uses a descriptive qualitative approach with the documentary method. The data collected was then analyzed using the historical and critical isnad methods. The result of this study is that in the history of the development of legal doctrine, the starting point of Islamic jurisprudence was from the late period of the Umayyad dynasty (132 H.). At this time isnād began to be used. The ancient schools of law made living traditions the source of their laws. Each generation in the Islamic region (Iraq, Hijaz, and Syria) has an agreed legal doctrine. Initially this doctrine was general in nature, only representing the opinion of the group (anonymous). But since the decades of the second century, the legal doctrines of the living tradition have been projected onto the great figures of the past who can be chosen at random. This projection then generates alternative names that can be used interchangeably. In this section, in particular, the quality of criticism of Schacht's hadith thinking can be seen.